LEGAL POWERS OF CITIZENS' SELF-GOVERNMENT BODIES IN ENVIRONMENTAL PROTECTION IN UZBEKISTAN - Suvankulov Jamshid Abdulahadovich (Web of Journals Publishing, 2025)
The article analyzes the problems of increasing the role of local governments in the implementation of the powers of citizens' self-government bodies in the field of environmental protection.
Keywords: Environmental protection, environmental powers of citizens' self-government bodies, powers of citizens' assemblies on issues of legal protection of nature.